A Study of Charged Cylindrical Gravitational Collapse with Dissipative Fluid - Sanjukta Chakraborty; Subenoy Chakraborty (Advances in High Energy Physics)
The present works deals with gravitational collapse of cylindrical viscous heat conducting anisotropic fluid following the work of Misner and Sharp. Using Darmois matching conditions, the dynamical equations are derived and the effects of charge and dissipative quantities over the cylindrical collapse are analyzed. Finally, using the Miller-Israel-Steward causal thermodynamic theory, the transport equation for heat flux is derived and its influence on collapsing system has been studied.